Synergistic activation of transcription by the human estrogen receptor bound to tandem responsive elements. - Ponglikitmongkol, M (1990)
The synergistic action of the human estrogen receptor (hER) has been investigated using minimal promoters containing a TATA region and one or two estrogen responsive elements (EREs). We find that paired perfectly palindromic EREs act additively and independently of their relative spacing when positioned close to the TATA box. However, when moved 175 bp further upstream, perfectly palindromic EREs act synergistically and in a stereoalignment-dependent manner. Less efficient imperfectly palindromic EREs display a stereoalignment-dependent synergism even when positioned close to the TATA box. Analysis of binding in vitro of the hER to perfectly or imperfectly palindromic EREs by gel retardation and nitrocellulose filter binding assays does not provide any evidence for cooperative DNA binding. Conversely, the human progesterone receptor (hPR) clearly shows cooperative binding to paired responsive elements (PREs) under similar conditions in vitro. Thus, hER molecules bound to adjacent EREs must be properly stereoaligned to activate transcription synergistically in vivo. However, our data suggest that this synergism is not primarily due to cooperative binding to the EREs.